Correlation Between Aeroallergen Levels and New Diagnosis of Eosinophilic Esophagitis in New York City. Issue 1 (January 2017) - Fahey, Lisa; Robinson, Guy; Weinberger, Kate; Giambrone, Ashley E.; Solomon, Aliza B.
ABSTRACT: Objective: The relation between food allergies and eosinophilic esophagitis (EoE) is well established. Aeroallergens may also contribute to the development of EoE; however, there are limited data to support or refute this hypothesis. The objectives of this pilot study were to determine whether there is a seasonal variation in the onset of symptoms and/or diagnosis of EoE and whether these variations correlate with a specific pollen concentration within New York City. Methods: We performed a retrospective chart review to identify all pediatric patients at New York Presbyterian Weill Cornell Medical Center diagnosed with EoE between 2002 and 2012. Sixty-six patients were identified and 28 were excluded. Cases were classified by both date of initial symptoms and date of histologic diagnosis. Pollen counts from a certified New York City counting station and the percentage of EoE cases were collated monthly and seasonally and compared. Results: There was a seasonal variation in onset of symptoms and diagnosis of EoE, with the highest number of patients reporting onset of symptoms of EoE in July to September, and those being diagnosed with EoE in October to December. There was a seasonal correlation between peak levels of grass pollen and peak onset of EoE symptoms, which were both highest in July to September. The diagnosis of EoE peaked one season later. Conclusions: The study findings suggest that there is a correlation between specific aeroallergens and both the onset of symptoms and time of diagnosis of patients with EoE.